Medios digitales en redes sociales, una alternativa de trabajo para graduados en Comunicación Social de la Universidad Técnica de Babahoyo - Huacón Lara, Jordan Diego (2020)
New technologies, without a doubt, revolutionized the traditional media sector, with the internet being a new tool to reach new consumers, anywhere and at any time because people can access the network through multiple technological devices. Digital Media in social networks are a work alternative for Graduates in Social Communication both for those who obtained their degree at the Technical University of Babahoyo and at a general level, which, being immersed in this medium contributes to the acquisition of experience and above all stay up-to-date with knowledge that the digital age demands.